A phenotype for the α7 nicotinic acetylcholine receptor null mutant - Morley, Barbara J.; Rodriguez-Sierra, Jorge F. (Brain research, 2004)
The α7 nicotinic acetylcholine receptor (nAChR) is heavily expressed in the mammalian brain. On a molecular level, the α7 nAChR may have a diversity of functions, but it is not known if these molecular events translate into phenotypes. The null mutant mouse is viable and generally normal. Here, we report a phenotype for the α7 nAChR null mutant mouse. The α7 nAChR is obligatory for the synchronization of an important biological rhythm, the female estrous cycle. The female null mutant mouse has asynchronous estrous cycles and a reduced number of surviving pups. Female null mutants also demonstrate a reliable diversity in phenotype, suggesting an interaction between environment and gene expression. Real-time RT-PCR measurements of the α7 mRNA expression in reproductive tissues of wild-type mice suggest that the ovulatory dysfunction in null mutants is probably central in origin.